Respuesta :

gmany

Answer:

x = 2

Step-by-step explanation:

3 - x + 1 = 2              combine like terms

-x + (3 + 1) = 2

-x + 4 = 2           subtract 4 from both sides

-x  +4 - 4 = 2 - 4

-x = -2                 change the signs

x = 2

Answer:

x = 2

Step-by-step explanation:

3 - x + 1 = 2

Add the 3 and the 1

- x + 4 = 2

Subtract the 4 on both sides to isolate the -x

- x + 4 (- 4) = 2 - 4

- x = - 2

Divide both sides by - 1 (to get rid of the negative signs)

x = 2

Hope I helped!!